Consequences of insecurity in emergency telephone consultations: an experimental study in medical students (Swiss Medical Weekly, 2014)
QUESTION UNDER STUDY: Handling emergency telephone consultations (ETCs) is a challenging and very important task for doctors. The aims of the study were to document insecurity in medical students during ETCs and to identify the reasons for that insecurity. We hypothesised that insecurity is associated with advising more urgent action (e.g. advice to call for an ambulance) in ETCs. METHODS: We used ETCs with simulated patients (SPs), with each student randomly allocated two of four possible cases. After the training, 137 students reported on any insecurity that they had in the various ETC phases. We analysed the reasons for insecurity using descriptive statistics. The association between the students’ advice that urgent action was needed and their insecurity was analysed with Spearman rank correlation. RESULTS: Overall, 95% of the students felt insecure in at least one phase of their ETC. History taking was the phase in which students felt most insecure (63.1%), followed by the phase of analysing the information given by the patient (44.9%). Perceived insecurity was associated with more urgent advice in one case scenario (abdominal pain; correlation r = 0.46; p